Não importa se morrerem antes... de Marcílio Onofre: criação, colaboração e aspectos técnicos-interpretativos - Oliveira, Mariana Rodrigues de (2019)
This research proposes to offer some discussions on the relationship between composer and performer in the piece Não importa se morrerem antes… written by the Brazilian composer Marcílio Onofre (1982), for viola, rabeca (Brazilian fiddle) and string orchestra, as well it intends to show the elaboration of a proposal for the interpretation of the piece. In order to achieve this conclusions, we developed a wide bibliographical review, meetings with the composer, besides interviews and a study in the final score edited by the author-interpreter. This research resulted in an interpretative proposal built directly in contact with the composer, a reflection on the participation of this researcher in the process of collaboration with the Composer, an edition with fingerings, extended technique methods used for the study of the work and the debut of the piece with audiovisual record. The process of collaboration was fundamental for the exchange of knowledge and for the feature of the piece. Where the author and the composer shared experiments in sounds and interpretation.